PET material for plastic goblet and its processing and molding technology
By using atomic transfer radical (ATRP) polymerization to modify the organic nanosilica nucleating agent for PET goblets and using blow molds with angles for blow molding, the problems of insufficient crystallinity and complex edge curling process of PET goblets during blow molding are solved, and efficient and simplified production processes and improved material performance are achieved.
Patent Information
- Application Number
- CN202411202047.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-08-29
AI Technical Summary
The existing PET goblets have insufficient crystallinity or excessive stretching during blow molding, and the edge curling process is complicated and costly, which has problems such as high energy consumption, high equipment cost and high operation difficulty.
The organic nanosilicon dioxide surface was modified by atom-transfer radical (ATRP) polymerization to prepare an organic nanosilicon dioxide nucleating agent with grafted ionomers, and the cup blank was blow-molded using a blow-molding mold with an angle, eliminating the step of rolling.
It improves the crystallinity and mechanical properties of PET materials, simplifies the process flow, reduces production costs, and achieves efficient production efficiency.
Smart Images

Figure CN119081363B_ABST
Abstract
Description
[0001] The invention relates to the field of polymer materials, in particular to a PET material for a plastic goblet and a processing and molding process thereof. Background Art
[0002] A goblet is a cup with a high base and a large body, commonly used for drinking red wine, champagne and other drinks. According to the material, goblets can be divided into glass, crystal, plastic, etc. PET (polyethylene terephthalate) is a common material for making plastic goblets. It is light and not easy to break, suitable for daily and outdoor use.
[0003] Blow molding is the most important step in the molding of PET goblets and bowls. Blow molding often requires stretching to improve the crystallinity of the material. If the stretching is not enough, the crystallinity of the product is not enough. If the stretching ratio is too large, the product will crack. In order to improve the performance of PET materials in the stretch blow molding process and the quality of the final product, it is generally necessary to add a certain amount of nucleating agent. Existing nucleating agents can be divided into inorganic small molecules, organic small molecules, and organic polymers according to their chemical composition. At present, inorganic powders including silica have the effect of promoting crystallization of polyester materials, but silica has poor dispersibility and is easy to aggregate. The nucleation rate of organic small molecules and organic ionomers is low and the thermal stability is poor. The most common method at present is to use polymer-coated nano-silica, which can be evenly dispersed in PET, but the outer layer is a neutral polymer and the nucleation efficiency is low.
[0004] The edge of the PET goblet is not specially treated, and the original cutting state is maintained without curling. The edge of the cup mouth is curled to form a curled goblet with a smooth edge. The non-curled goblet is simple to make and low in cost, but there may be sharp edges, and the user experience is relatively poor. The curled goblet is comfortable to drink and reduces the risk of cuts, but the production process is relatively complicated and the cost is slightly higher. At present, there are mainly the following curling processes: a) hot curling: use a heating device to heat and soften the edge of the cup mouth, and then roll up the edge through a mold; b) mechanical curling: use a special curling machine to roll up the edge of the cup mouth through mechanical force; c) flame curling: use a high-temperature flame to quickly heat the cup mouth, and then curl it; d) ultrasonic curling: use ultrasonic energy to partially melt the edge of the cup mouth, and then curl it. Some of these methods have high energy consumption and require additional heating equipment; some are prone to cause tiny cracks, affecting the service life of the product; some are difficult to accurately control the degree of heating, which is easy to cause overburning or insufficient heating; some equipment costs are high and require high technical requirements for operators. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the present invention modifies the surface of organic nano-silica by atom transfer radical (ATRP) polymerization to obtain an organic nano-silica nucleating agent for grafted ionomers, which has good compatibility and dispersibility with PET materials, high nucleation efficiency and a certain improvement in material properties. A blow molding mold with an angle is used to blow mold the cup blank, which eliminates the curling step and simplifies the process flow.
[0006] The technical solution of the present invention is as follows: a PET material for a plastic goblet, the PET material comprises, by weight: 95-98 parts of PET, 0.5-3 parts of a nucleating agent, and 1-2 parts of a thermal stabilizer; the preparation method of the nucleating agent is as follows:
[0007] 1) Preparation of organic nano-silica: In a reaction kettle, add 1 part of siloxane and dissolve it in a mixed solution of 30-40 parts of N,N-dimethylformamide and 15-20 parts of methanol, then add 0.7-0.8 parts of ammonium hydroxide and 1.0-1.1 parts of distilled water in sequence, seal, heat and stir at 50-60° C. for 24 hours to obtain a colorless transparent liquid, remove the solvent to obtain an organic nano-silica with hydroxyl and amino groups on the surface;
[0008] 2) preparing an organic nano-silica initiator: dispersing 1 part of the organic nano-silica obtained in step 1) in 20-25 parts of anhydrous dichloromethane solvent, ultrasonicating for 15-30 minutes, transferring to a reactor, adding 2.5-3 parts of triethylamine, bubbling the solution with argon for 3-5 minutes, dissolving 1.5-2.0 parts of an acylating agent in anhydrous dichloromethane solvent at 0-5°C and slowly dropping into the reactor, reacting at room temperature for 20-24 hours, washing three times with dilute hydrochloric acid solution, distilled water and saturated sodium bicarbonate aqueous solution respectively after the reaction is completed, drying with anhydrous magnesium sulfate, collecting the organic phase, and removing the solvent to obtain an organic nano-silica initiator;
[0009] 3) Preparation of nucleating agent: Disperse 1 part of the organic nano-silica initiator obtained in step 2) in 30-35 parts of anhydrous anisole solvent, transfer to a reaction kettle after ultrasonication for 15-30 minutes, add 20-25 parts of acrylate monomer and 0.01-0.015 parts of cuprous bromide, freeze-thaw degassing three times, add 0.15-0.22 parts of N,N,Nˋ,Nˋ,Nˋˋ-pentamethyldiethylenetriamine ligand under nitrogen atmosphere, and heat at 60-65°C. The mixture was stirred for 6 to 8 hours, and then 5 to 10 parts of maleic anhydride monomer were added under nitrogen atmosphere. After stirring for 6 to 8 hours, oxygen was introduced to terminate the polymerization reaction. The oxidized copper ions were removed by washing with distilled water, the organic phase was collected, concentrated by rotary evaporation, dispersed in a mixed solution of aqueous sodium hydroxide solution and methanol, stirred at 25 to 40°C for 1 to 2 hours, and methanol was removed by rotary evaporation. The mixture was extracted with dichloromethane solvent for three times, the organic phase was collected, concentrated by rotary evaporation, precipitated in cold methanol, filtered, and dried to obtain a nucleating agent.
[0010] Preferably, the PET is food grade PET.
[0011] Preferably, the heat stabilizer is at least one of a calcium zinc stabilizer and epoxidized soybean oil.
[0012] Preferably, the siloxane in step 1) is at least one of 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane.
[0013] Preferably, the acylating agent in step 2) is one or more of chloroacetyl chloride, bromoacetyl chloride, and bromoacetyl bromide;
[0014] More preferably, the acylating agent in step 2) is chloroacetyl chloride.
[0015] Preferably, the acrylate monomer in step 3) is one or more of ethyl acrylate and methyl acrylate.
[0016] More preferably, the acrylate monomer in step 3) is ethyl acrylate.
[0017] Preferably, the concentration of the sodium hydroxide aqueous solution in step 3) is 1-2 mol / L; the volume ratio of the sodium hydroxide aqueous solution to methanol in the mixed solution is (1:2)-(2:1).
[0018] The present invention also discloses a plastic goblet processing and forming process, comprising the following steps:
[0019] S1. Preparation of sheet: The PET material is mixed and then fed into an extruder to extrude a PET sheet;
[0020] S2. Preparation of cups and bowls: The PET sheet obtained in S1 is molded into a cup blank through a molding mold, and after cooling, it is placed in a blow mold with an angle for preheating, and a cup and bowl with a curled edge is obtained by stretching, pre-blowing, high blowing, cooling, and mold opening;
[0021] S3. Preparation of cup feet and base: After the PET material is mixed evenly, it is injected into the mold of the cup feet and base through an injection molding machine, and the cup feet and base are obtained by cooling, curing, and opening the mold;
[0022] S4. Combined high-heeled glass: The cup bowl and the cup foot are combined under pressure by hot melting, and the high-heeled glass is obtained after punching and shearing.
[0023] The PET material is the PET material for the plastic goblet.
[0024] Preferably, the blow molding mold includes a main body, a fixed part and a blow molding part, the main body has a mold cavity, and the cup blank is added to the mold cavity; the fixed part includes an upper mold 20 and a lower mold 30, wherein the upper mold 20 and the lower mold 30 are relatively clamped and define an angle 31; the blow molding part includes a stretching core rod 10 and a blow tube 11, and the blow molding part is arranged in the upper mold 20 and inserted into the mold cavity.
[0025] Specifically, the mold cavity is not limited to the shape shown in the drawings. In a specific embodiment, the mold cavity can be a Bordeaux cup-shaped mold cavity, a Burgundy cup-shaped mold cavity, a tulip-shaped champagne cup-shaped mold cavity, a shallow dish champagne cup-shaped mold cavity, a white wine cup-shaped mold cavity, a sweet wine glass-shaped mold cavity, a Chardonnay wine glass-shaped mold cavity, a Sherry wine glass-shaped mold cavity, a Port wine glass-shaped mold cavity, etc.
[0026] An angle is arranged between the upper mold and the lower mold of the present invention, so that a cup or bowl with a curled edge can be directly obtained during blow molding.
[0027] Specifically, the extrusion temperature in step S1 is 240-280°C, and the screw speed is 50-80rpm; the molding temperature in step S2 is 250-280°C, the preheating temperature is 90-110°C, the stretching temperature is 90-100°C, the stretching length is 80-90mm, the blow molding temperature is 100-120°C, the pre-blowing pressure is 1-1.3Mpa, and the high blow pressure is 3.5-4.5Mpa; the injection temperature in step S3 is 260-280°C, and the injection pressure is 80-120Mpa; the pressurization bonding temperature in S4 is 200-230°C, and the pressurization pressure is 0.3-0.5Mpa.
[0028] Beneficial Effects
[0029] The present invention has the following beneficial effects:
[0030] (1) The cup blank is blow-molded by a blow molding mold with an angle, which eliminates the curling step, simplifies the process flow, and improves production efficiency.
[0031] (2) The modified organic nano-silica nucleating agent is a synergistic nucleation of organic nano-silica and ionomer. In addition to the nucleation effect, the ionomer also plays a role in improving the dispersibility and compatibility of the nucleating agent, while the organic nano-silica plays a role in enhancing the stability of the nucleating agent and improving the mechanical properties of PET.
[0032] (3) The inner core is homemade organic nano-silica, which has more reaction sites than commercially available nano-silica, in addition to unreacted hydroxyl groups. It also has a large number of amino groups on its surface. After modification with an acylating agent, it is polymerized by ATRP and hydrolyzed to obtain surface-modified organic nano-silica. Compared with ordinary nano-silica, homemade organic nano-silica has more reaction sites, can be grafted with more polymer chains, has better dispersibility, and is not easy to aggregate. Alkyl chains are introduced into the homemade organic nano-silica to further enhance the toughness of the inner core.
[0033] (4) Adding nucleating agents can increase the crystallization rate of PET, improve production efficiency, improve transparency and gloss, and improve the tensile and other mechanical properties of PET. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The structure and synthesis diagram of the nucleating agent of the present invention;
[0035] Figure 2 is the infrared spectrum of the synthetic product in the present invention;
[0036] Figure 3 is the hydrodynamic diameter of the organic nano-silicon dioxide and the nucleating agent in the present invention;
[0037] Figure 4 These are the melting and crystallization curves of different materials in the present invention.
[0038] Figure 5 This is a schematic diagram of the blow molding mold structure of the present invention;
[0039] In the figure, 10. stretching mandrel, 11. blowpipe, 20. upper die, 30. lower die, 31. angle; DETAILED DESCRIPTION
[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0042] The raw materials and equipment used in the embodiments and comparative examples are described as follows:
[0043] PET: Food grade PET resin, brand FG-530, DuPont;
[0044] Heat stabilizer: calcium zinc stabilizer, brand CF128, Hubei Chengfeng Chemical Co., Ltd.;
[0045] 3-Aminopropyltriethoxysilane: product number A800523, purchased from Shanghai MacLean Biochemical Technology;
[0046] Chloroacetyl chloride: product number C804574, purchased from Shanghai MacLean Biochemical Technology;
[0047] Cuprous bromide: product number C804582, purchased from Shanghai MacLean Biochemical Technology;
[0048] N,N,Nˋ,Nˋ,Nˋˋ-Pentamethyldiethylenetriamine: product number N822749, purchased from Shanghai MacLean Biochemical Technology;
[0049] Maleic anhydride: product number M821319, purchased from Shanghai MacLean Biochemical Technology;
[0050] Ethyl acrylate: product number E809084, purchased from Shanghai MacLean Biochemical Technology;
[0051] Commercially available nano-silica 1: particle size 7 nm, purchased from Zhejiang Manli Nanotechnology Co., Ltd.;
[0052] Commercially available nano-silicon dioxide 2: particle size 20 nm, purchased from Zhejiang Manli Nanotechnology Co., Ltd.
[0053] PEA-MA (Polyethyl acrylate-maleic acid copolymer)
[0054] In a reaction kettle, 20 parts of ethyl acrylate and 0.01 parts of cuprous bromide were added respectively, and the mixture was degassed by freeze-thaw for three times. Under a nitrogen atmosphere, 0.15 parts of N,N,Nˋ,Nˋ,Nˋˋ-pentamethyldiethylenetriamine ligand was added. The mixture was heated at 60°C and stirred for 6 hours. Then, 5 parts of maleic anhydride monomer were added under a nitrogen atmosphere. After stirring for 6 hours, oxygen was introduced to terminate the polymerization reaction. The oxidized copper ions were removed by washing with distilled water, the organic phase was collected, concentrated by rotary evaporation, dispersed in a mixed solution of aqueous sodium hydroxide solution and methanol, stirred at 25°C for 2 hours, and methanol was removed by rotary evaporation. The mixture was extracted with dichloromethane solvent for three times, the organic phase was collected, concentrated by rotary evaporation, precipitated in cold methanol, filtered, and dried to obtain PEA-MA.
[0055] Organic Nano Silica
[0056] In a reaction kettle, add 1 part of siloxane and dissolve it in a mixed solution of 30 parts of N,N-dimethylformamide and 20 parts of methanol, then add 0.8 parts of ammonium hydroxide and 1.05 parts of distilled water in sequence. After sealing, heat and stir at 50°C for 24 hours to obtain a colorless transparent liquid. Remove the solvent to obtain organic nano-silica with hydroxyl and amino groups on the surface.
[0057] Organic nano-silica initiator 1
[0058] Disperse 1 part of the obtained organic nano-silica in 25 parts of anhydrous dichloromethane solvent, ultrasonicate for 15 to 30 minutes, transfer to a reactor, add 3 parts of triethylamine, use argon to bubble the solution for 5 minutes, dissolve 2.0 parts of chloroacetyl chloride in anhydrous dichloromethane solvent at 0 degrees Celsius and slowly add it dropwise to the reactor, react at room temperature for 24 hours, and after the reaction is completed, wash three times with dilute hydrochloric acid solution, distilled water and saturated sodium bicarbonate aqueous solution respectively, dry with anhydrous magnesium sulfate, collect the organic phase, and remove the solvent to obtain an organic nano-silica initiator.
[0059] Organic nano-silica initiator 2
[0060] Compared with the organic nano-silica initiator 1, the difference is that the organic nano-silica is replaced by the commercially available nano-silica 1.
[0061] Nucleating agent 1
[0062] One part of the obtained organic nano-silica initiator 1 was dispersed in 30 parts of anhydrous anisole solvent, and after ultrasonic treatment for 15 minutes, it was transferred to a reactor, and 20 parts of ethyl acrylate and 0.01 parts of cuprous bromide were added respectively. The reaction was freeze-thawed and degassed three times. Under a nitrogen atmosphere, 0.15 parts of N,N,Nˋ,Nˋ,Nˋˋ-pentamethyldiethylenetriamine ligand was added. The mixture was heated at 60°C and stirred for 6 hours. Then, under a nitrogen atmosphere, 5 parts of maleic anhydride monomer were added. After stirring for 6 hours, oxygen was introduced to terminate the polymerization reaction. The oxidized copper ions were removed by washing with distilled water, the organic phase was collected, concentrated by rotary evaporation, dispersed in a mixed solution of sodium hydroxide aqueous solution and methanol, stirred at 25°C for 2 hours, and methanol was removed by rotary evaporation. The mixture was extracted with dichloromethane solvent three times, the organic phase was collected, concentrated by rotary evaporation, precipitated in cold methanol, filtered, and dried to obtain the nucleating agent 1.
[0063] Nucleating agent 2
[0064] One part of the obtained organic nano-silica initiator 1 was dispersed in 35 parts of anhydrous anisole solvent, and after ultrasonic treatment for 30 minutes, it was transferred to a reactor, and 25 parts of ethyl acrylate and 0.015 parts of cuprous bromide were added respectively. The reaction was freeze-thawed and degassed three times. Under a nitrogen atmosphere, 0.22 parts of N,N,Nˋ,Nˋ,Nˋˋ-pentamethyldiethylenetriamine ligand was added. The mixture was heated at 65°C and stirred for 8 hours. Then, 10 parts of maleic anhydride monomer were added under a nitrogen atmosphere. After stirring for 8 hours, oxygen was introduced to terminate the polymerization reaction. The oxidized copper ions were removed by washing with distilled water. The organic phase was collected, concentrated by rotary evaporation, dispersed in a mixed solution of sodium hydroxide aqueous solution and methanol, stirred at 40°C for 1 hour, and methanol was removed by rotary evaporation. The mixture was extracted with dichloromethane solvent three times, the organic phase was collected, concentrated by rotary evaporation, precipitated in cold methanol, filtered, and dried to obtain the nucleating agent 2.
[0065] Nucleating agent 3
[0066] Compared with nucleating agent 2, the difference is that organic nano-silica initiator 1 is replaced by organic nano-silica initiator 2.
[0067] The following is the test method of the performance parameters involved in the present invention:
[0068] (1) Melt strength: The PET sheet was put into a melt extensional rheometer for testing at an extrusion temperature of 280 °C, a rate of 0.5 g / min, and a stretching speed of 15 m / min.
[0069] (2) Crystallization behavior: differential scanning calorimetry, cooling rate 10 °C / min;
[0070] (3) Tensile strength: PET sheets were blown into films, cut into samples, and tested according to GB / T 1040.3-2006 “Determination of tensile properties of plastics Part 3: Test conditions for films and sheets”;
[0071] (4) Nominal strain at break: PET sheets were blown into films, cut into samples, and measured according to GB / T 1040.3-2006 “Determination of tensile properties of plastics Part 3: Test conditions for films and sheets”.
[0072] (5) Light transmittance test: PET sheets were blown into films, cut into samples, and tested according to GB / T 2410-2008 “Determination of light transmittance and haze of transparent plastics”.
[0073] (6) Gloss test: PET sheets were blown into films, cut into samples, and tested according to GB / T 8807-1988 “Test method for specular gloss of plastics”.
[0074] Depend on Figure 2 The infrared spectrum shows that after the synthesis of organic nano-silica, 1045cm -1 The peak is Si-O-Si, 3300 cm -1 The peak is Si-OH. In the organic nano-silica initiator, hydroxyl reacts with amino, 1526cm -1 With 1715cm -1 The peaks of amide and ester groups are 3390 cm after polymerization and hydrolysis. -1 The peak is that of carboxyl group.
[0075] Depend on Figure 3 The data of fluid dynamic diameter measured by dynamic light scattering show that the particle size changes from 6nm to 17nm after grafting, which further proves that the polymer is successfully grafted onto organic nano-silica.
[0076] The molding process of plastic goblet processing includes the following steps:
[0077] S1. Preparation of sheet: PET, nucleating agent and heat stabilizer are mixed and then fed into an extruder, the extrusion temperature is 240 to 280 ° C, the screw speed is 50 to 80 rpm and extruded into a PET sheet;
[0078] S2. Preparation of cups and bowls: The PET sheet obtained in S1 is molded into a cup blank at a molding temperature of 250-280°C through a molding mold, and after cooling, it is placed in a blow molding mold with an angle for preheating at a temperature of 90-110°C, and stretched at a temperature of 90-100°C and a length of 80-90mm, pre-blown at a pressure of 1-1.3Mpa, high blown at a pressure of 3.5-4.5Mpa, cooled, and opened to obtain a cup bowl with a curled edge;
[0079] S3. Preparation of cup feet and base: PET, nucleating agent and heat stabilizer are injected into the mold of cup feet and base by an injection molding machine at a temperature of 260 to 280 ° C and a pressure of 80 to 120 MPa, and the cup feet and base are obtained by cooling, curing and opening the mold;
[0080] S4. Combined high-heeled glass: The cup bowl and the cup foot are pressurized and combined by hot melting at a temperature of 200-230℃ and a pressure of 0.3-0.5Mpa, and the high-heeled glass is obtained after punching and shearing.
[0081] Table 1 Plastic goblet formula, Examples 1 to 7 (mass / kg)
[0082] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 PET 98 95 97.5 97 96.5 96 97 Nucleating agent 1 0.5 3 1 1.5 2 2.5 Nucleating agent 2 1.5 Heat Stabilizer 1 2 1 1 1 1 1
[0083] Table 2 Plastic goblet formula, comparative examples 1 to 5 (mass / kg)
[0084] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 PET 97 97 97 98.5 92 Commercially available nano-silicon dioxide 2 1.5 5.5 PEA-MA 1.5 Nucleating agent 3 1.5 Heat Stabilizer 1 1 1 1 1
[0085] Table 3 Physical properties test
[0086]
[0087]
[0088] It can be seen from the data of the embodiments and comparative examples that the appropriate addition of the nucleating agent prepared in the present invention can effectively enhance the melt strength of the PET material, increase the crystallization temperature after cooling after melting, enhance the crystallization performance, and improve the tensile properties and nominal strain at break, and have good light transmittance and glossiness, so that the prepared plastic goblet has the texture of a glass cup while also meeting the strength requirements.
[0089] From the data of Examples 1, 3, 4, 5, and 6 in Table 3, it can be seen that with the increase of the content of the nucleating agent, the melt strength, tensile strength, and nominal strain at break first increase and then decrease, but the melt crystallization temperature gradually increases, and the transmittance and gloss increase, indicating that the crystallization ability has been increasing, but too high a crystallinity will also reduce the performance of the material; from the data of Examples 4 and 7, it can be seen that when the content of MA in the nucleating agent is too high, the melt strength, tensile strength, and nominal strain at break of the material will all decrease, but the crystallization ability will be enhanced, and the transmittance is better. Although MA can be effectively It can enhance the crystallization ability, but excessive presence will also lead to the breakage of PET chains and a decrease in glossiness, thereby reducing the performance of the material; from the data of Comparative Examples 1, 2, and 4, it can be seen that the addition of PEA-MA and nano-silica alone improves the performance of the material, but the effect is not as good as nucleating agents 1 and 2; from the data of Comparative Example 3, it can be seen that nucleating agent 3 obtained by modifying commercially available nano-silica is not as good as nucleating agents 1 and 2 in improving performance. This is presumably because there are too few active points on the surface of commercially available nano-silica, fewer grafted PEA-MA chains, and poor internal flexibility.
[0090] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A PET material for a plastic goblet, characterized in that: The PET material comprises, by weight: 95-98 parts of PET, 0.5-3 parts of nucleating agent, and 1-2 parts of thermal stabilizer; the preparation method of the nucleating agent is as follows: 1) Preparation of organic nano-silica: In a reaction kettle, add 1 part of siloxane and dissolve it in a mixed solution of 30-40 parts of N,N-dimethylformamide and 15-20 parts of methanol, then add 0.7-0.8 parts of ammonium hydroxide and 1.0-1.1 parts of distilled water in sequence, seal, heat and stir at 50-60° C. for 24 hours to obtain a colorless transparent liquid, remove the solvent to obtain an organic nano-silica with hydroxyl and amino groups on the surface; 2) preparing an organic nano-silica initiator: dispersing 1 part of the organic nano-silica obtained in step 1) in 20-25 parts of anhydrous dichloromethane solvent, ultrasonicating for 15-30 minutes, transferring to a reactor, adding 2.5-3 parts of triethylamine, bubbling the solution with argon for 3-5 minutes, dissolving 1.5-2.0 parts of an acylating agent in anhydrous dichloromethane solvent at 0-5°C and slowly dropping into the reactor, reacting at room temperature for 20-24 hours, washing three times with dilute hydrochloric acid solution, distilled water and saturated sodium bicarbonate aqueous solution respectively after the reaction is completed, drying with anhydrous magnesium sulfate, collecting the organic phase, and removing the solvent to obtain an organic nano-silica initiator; 3) Preparation of nucleating agent: Disperse 1 part of the organic nano-silica initiator obtained in step 2) in 30-35 parts of anhydrous anisole solvent, transfer to a reaction kettle after ultrasonication for 15-30 minutes, add 20-25 parts of acrylate monomer and 0.01-0.015 parts of cuprous bromide, freeze-thaw degassing three times, add 0.15-0.22 parts of N,N,Nˋ,Nˋ,Nˋˋ-pentamethyldiethylenetriamine ligand under nitrogen atmosphere, and heat at 60-65°C. The mixture was stirred for 6 to 8 hours, and then 5 to 10 parts of maleic anhydride monomer were added under nitrogen atmosphere. After stirring for 6 to 8 hours, oxygen was introduced to terminate the polymerization reaction. The oxidized copper ions were removed by washing with distilled water, the organic phase was collected, concentrated by rotary evaporation, dispersed in a mixed solution of aqueous sodium hydroxide solution and methanol, stirred at 25 to 40°C for 1 to 2 hours, and methanol was removed by rotary evaporation. The mixture was extracted with dichloromethane solvent for three times, the organic phase was collected, concentrated by rotary evaporation, precipitated in cold methanol, filtered, and dried to obtain a nucleating agent.
2. The PET material for a plastic goblet as claimed in claim 1, characterized in that: The PET is food grade PET.
3. The PET material for a plastic goblet as claimed in claim 1, characterized in that: The heat stabilizer is at least one of a calcium zinc stabilizer and epoxy soybean oil.
4. The PET material for a plastic goblet as claimed in claim 1, characterized in that: The siloxane in step 1) is at least one of 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane; the acylating agent in step 2) is one or more of chloroacetyl chloride, bromoacetyl chloride and bromoacetyl bromide; the acrylate monomer in step 3) is one or more of ethyl acrylate and methyl acrylate.
5. The PET material for a plastic goblet as claimed in claim 1, characterized in that: The concentration of the sodium hydroxide aqueous solution in step 3) is 1-2 mol / L; the volume ratio of the sodium hydroxide aqueous solution to methanol in the mixed solution is (1:2)-(2:1).
6. A plastic goblet processing and molding process, characterized in that: The plastic goblet is obtained by processing the PET material according to any one of claims 1 to 5, and the processing and molding process of the plastic goblet comprises the following steps: S1. Preparation of sheet: The PET material is mixed and then fed into an extruder to extrude a PET sheet; S2. Preparation of cups and bowls: The PET sheet obtained in S1 is molded into a cup blank through a molding mold, and after cooling, it is placed in a blow mold with an angle for preheating, and a cup and bowl with a curled edge is obtained by stretching, pre-blowing, high blowing, cooling, and mold opening; S3. Preparation of cup feet and base: After the PET material is mixed evenly, it is injected into the mold of the cup feet and base through an injection molding machine, and the cup feet and base are obtained by cooling, curing, and opening the mold; S4. Combined high-heeled glass: The cup bowl and the cup foot are combined under pressure by hot melting, and the high-heeled glass is obtained after punching and shearing.
7. A plastic goblet processing and forming process as claimed in claim 6, characterized in that: The blow molding mold comprises a main body, a fixed part and a blow molding part, wherein the main body has a mold cavity, and the cup blank is added into the mold cavity; the fixed part comprises an upper mold (20) and a lower mold (30), wherein the upper mold (20) and the lower mold (30) are relatively clamped and define an angle (31); the blow molding part comprises a stretching core rod (10) and a blow pipe (11), and the blow molding part is arranged in the upper mold (20) and inserted into the mold cavity.
8. A plastic goblet processing and forming process as claimed in claim 6, characterized in that: The extrusion temperature in step S1 is 240-280°C, and the screw speed is 50-80rpm; the molding temperature in step S2 is 250-280°C, the preheating temperature is 90-110°C, the stretching temperature is 90-100°C, the stretching length is 80-90mm, the blow molding temperature is 100-120°C, the pre-blow pressure is 1-1.3Mpa, and the high blow pressure is 3.5-4.5Mpa; the injection temperature in step S3 is 260-280°C, and the injection pressure is 80-120Mpa; the pressurization bonding temperature in S4 is 200-230°C, and the pressurization pressure is 0.3-0.5Mpa.
Citation Information
Patent Citations
Organic metal hybrid nucleating agent and preparation method and application thereof
CN112851955A
Nano composite nucleating agent for thermoplastic plastic, preparation method and application of nano composite nucleating agent in polypropylene
CN113773550A